2020
DOI: 10.1111/jipb.13009
|View full text |Cite
|
Sign up to set email alerts
|

N4‐methylcytidine ribosomal RNA methylation in chloroplasts is crucial for chloroplast function, development, and abscisic acid response in Arabidopsis

Abstract: Although the essential role of messenger RNA methylation in the nucleus is increasingly understood, the nature of ribosomal RNA (rRNA) methyltransferases and the role of rRNA methylation in chloroplasts remain largely unknown. A recent study revealed that CMAL (for Chloroplast mr aW‐ Like) is a chloroplast‐localized rRNA methyltransferase that is responsible for N4‐methylcytidine (m4C) in 16S chloroplast rRNA in Arabidopsis thaliana. In this study, we further examined the role of CMAL in chloroplast biogenesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Along with this, chloroplast-to-nucleus signal affects the expression of plant hormone (GA, auxin, and ABA) signalingrelated genes. This study indicates that all these CMAL-mediated processes are essential for plant development and hormone signaling (Tieu Ngoc et al, 2021). Another study (Zou et al, 2020) in Arabidopsis showed that CMAL is involved in plant development by modulating auxin signaling pathways, in which authors uncovered the role of CMAL in ribosome biogenesis (Zou et al, 2020).…”
Section: Ribosomal Rna Methylation Is Crucial For Chloroplast Functio...mentioning
confidence: 70%
“…Along with this, chloroplast-to-nucleus signal affects the expression of plant hormone (GA, auxin, and ABA) signalingrelated genes. This study indicates that all these CMAL-mediated processes are essential for plant development and hormone signaling (Tieu Ngoc et al, 2021). Another study (Zou et al, 2020) in Arabidopsis showed that CMAL is involved in plant development by modulating auxin signaling pathways, in which authors uncovered the role of CMAL in ribosome biogenesis (Zou et al, 2020).…”
Section: Ribosomal Rna Methylation Is Crucial For Chloroplast Functio...mentioning
confidence: 70%
“…Although some abiotic stress responses have been reported, ribosome biogenesis can adapt to these stresses by increasing the transcript levels of respective key genes. However, the role of ribosome biosynthesis in plant immunity has rarely been reported ( Yu H. et al, 2020 ; Tieu Ngoc et al, 2021 ). In this study, compared to WT_24 h, gmsweet15 _24 h upregulated the abundance of genes related to ribosome biosynthesis ( Figures 4A , C ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides their hydrogen bonding ability, they can also generate π-π interactions. The last compound is a cytosine nucleoside analogue, which has mechanisms to inhibit DNA methyltransferase (e.g., zebularine) and potential antimetabolic and antitumor activities [63]. It also has a comparatively stable binding pocket with the protein EPAS1 through more than four potential hydrogen bonds (Figure 8E).…”
Section: Five Compounds Were Identified To Target the Tf Epas1mentioning
confidence: 99%